1. The problem statement, all variables and given/known data solve differential equation xdy + (xy+y-1)dx=0 2. Relevant equations dy/dx + P(x)y = Q(x) u = exp[int(P(x)] - integrating factor exp[int(P(x))]*[dy/dx+P(x)y = Q(x)] => d/dx[P(x)]y = exp[int(P(x))]Q(x) int[d/dx[P(x)]y = exp[int(P(x))]Q(x)] solution is with respect to y. 3. The attempt at a solution xdy = -(xy+y-1)dx dy/dx = (1-y+xy)/x dx/dy = x/(1-y+xy) dx/dy = x-x/y+1/y dx/dy - x + x/y = 1/y I'm stuck here, I'm just not sure who to get the equation into a linear form where I could take the integrating factor and solve for x in the case since I switched the dependent variables to see if that wouldn't make it more complicated, any help from that point on would be greatly appreciated.